Technology for implementing the lean six sigma quality management model in higher education institutions. Part 2: Inconsistencies analysis, educational process improvement and control of improvements sustainability - Zaporozhets, O. V.; Moshchenko, I. O. (ХНУРЕ, 2024)
The relevance of the application of the newest quality management technologies, namely the Lean Six Sigma (LSS) methodology in ensuring the educational process quality in higher education institutions (HEIs) in accordance with the guidelines of DSTU ISO 21001:2019 Educational organizations – Management systems for educational organizations – Requirements with guidance for use (ISO 21001:2018, IDT) and Standards and Guidelines for Quality Assurance in the European Higher Education Area (ESG) is substantiated. The current state of development the problem of the production-oriented quality management model LSS adaptation to the conditions of HEIs functioning is analyzed in the works of foreign and Ukrainian scientists. The purpose of the article is to analyze the conditions for the LSS model implementation in HEIs in order to increase the efficiency of educational and scientific business processes and the applied implementation of LSS technologies taking into account the peculiarities of the Ukrainian educational environment. The practical significance of the article is to improve the quality of educational services delivery in HEIs using the continuous improvement cycle DMAIC and LSS tools on the example of increasing the effectiveness of the key process “Development EMS for the educational process”. Critical to quality characteristics (CTQC) of the educational product “Complex of Educational and Methodological Support (CEMS)” have been established. Current and target CTQC values are defined. A critical analysis of the CTQC non-compliance causes with the target value was carried out using FMEA analysis and Value Stream Mapping (VSM). Practical measures to improve the process quality are proposed. Process quality indicators were calculated after the implementation of corrective measures in the educational process. The prospects of the study are the application of DMAIC technology and other tools for the implementation of the LSS quality management methodology to improve the efficiency of all key educational and scientific business processes within the framework of the development of a comprehensive model of the HEIs quality management in accordance with the principles of modern International and European standards in the field of education.
Keywords: Lean Six Sigma (LSS); higher education institutions (HEIs); business process; Value Stream Map; FMEA